PHYSICAL EDUCATION IN SAHIH AL BUKHARI: INSIGHTS FROM THE HADITH - Bakti, Surya; Nahar, Syamsu; Arsyad, Junaidi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
This study aims to analyze the term physical education in the book of Sahih al-Bukhari, analyze the material of physical education in the book of Sahih al-Bukhari, and analyze the relevance of physical education in the book of Sahih al-Bukhari to contemporary Islamic education. This research method is a library research type. The results of the study show that there are a number of hadiths that explicitly or implicitly reflect the attention of the Prophet Muhammad. on physical education, namely hadith numbers 5649, 2684, 3122, 403, 2655, 2658, 6791, 5055, 3925, 1699, 6781 and 2920. Physical education by maintaining diet is found in hadith numbers 4959, 631, 5043, 5153 and 3893. Physical education with natural medicine is found in hadith numbers 5252, 854, 5807 and 1804. The material on sports education in the book of Sahih al-Bukhari, includes various types of relevant physical activities, such as wrestling, archery, horse riding, throwing. The material on physical education through natural medicine also contains several health practices taught by the Prophet Muhammad, such as the recommendation to drink honey, qailulah. The relevance of physical education in the book of Sahih al-Bukhari to contemporary Islamic education shows that the values ​​and practices of physical education in the hadiths of Sahih al-Bukhari are still very applicable today.